2022
DOI: 10.32670/fairvalue.v4i10.1642
|View full text |Cite
|
Sign up to set email alerts
|

Analisis good corporate governance terhadap pengungkapan ESG di Indonesia tahun 2016-2020

Abstract: The purpose of this study was to measure the effect of board size, women on the board, independent commissioners, remuneration committee, and audit quality on environmental, social, and governance (ESG) disclosures by companies in Indonesia. The ESG disclosure data used in this study comes from the Thomson Reuters database for a period of five years, from 2016-2020. The sampling method used was purposive sampling method, so that 39 sample companies were obtained for five years of observation (2016-2020) with 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…This is contrary to research conducted by Husted & Sousa-Filho, (2019) found that the female board of directors had a significant negative effect on environmental, social and governance disclosures. So is contrary to Septiana & Puspawati, (2022) find Negative female board of directors does not have a significant effect on environmental, social and governance disclosures. This shows that even though there is a high percentage of female directors, they are not yet able to influence the level of social disclosure, which indicates that women are more sensitive to social issues.…”
Section: The Influence Of Good Corporate Governance On Environmental ...contrasting
confidence: 57%
“…This is contrary to research conducted by Husted & Sousa-Filho, (2019) found that the female board of directors had a significant negative effect on environmental, social and governance disclosures. So is contrary to Septiana & Puspawati, (2022) find Negative female board of directors does not have a significant effect on environmental, social and governance disclosures. This shows that even though there is a high percentage of female directors, they are not yet able to influence the level of social disclosure, which indicates that women are more sensitive to social issues.…”
Section: The Influence Of Good Corporate Governance On Environmental ...contrasting
confidence: 57%
“…Thel implel mel ntatiol n ol f Gol ol d Col rpol ratel Gol vel rnancel col ntributel s tol improl ving thel financial pel rfol rmancel ol f thel col mpany which has a pol sitivel impact ol n El SG invel stmel nt (Affel s & Jarbol ui, 2023;Kim & Li, 2021; Mariel tza el t al., 2020; Trinh el t al., 2023). El SG invel stol rs tel nd tol lol ol k fol r col mpaniel s with gol ol d financial pel rfol rmancel , in linel with thel ir gol al ol f achiel ving gol ol d financial rel sults whilel col nsidel ring El SG factol rs(Sel ptiana & Puspawati, 2022). Thel rel fol rel , thel hypol thel sis ol f this study is: H1 : Col rpol ratel Gol vel rnancel has a pol sitivel el ffel ct ol n El SG invel stmel nt…”
mentioning
confidence: 72%
“…Sustainability reports are applied to issuers based on their sector from 2019 and will be applied as a whole in 2025 [5]. When a corporation discloses its performance, it does so by applying the ESG principles.…”
Section: Introductionmentioning
confidence: 99%